GAMBARAN KARAKTERISTIK DAN PENGETAHUAN IBU HAMIL TENTANG KELUARGA BERENCANA PASCA SALIN DI UPTD PUSKESMAS II DINAS KESEHATAN KECAMATAN DENPASAR SELATAN - Mardiah, Aynun Mardiah; Tirtawati , Gusti Ayu; Armini, Ni Wayan (Fakultas Ilmu Kesehatan, 2025)
Indonesia is a country that is rapidly growing in population. In order to reduce population growth, the government has implemented a family planning program for the community. The aim of this research is to determine the characteristics and knowledge of pregnant women about postpartum birth control. This research is a quantitative descriptive research with a cross-sectional approach, the population in this study is pregnant women at Community Health Center II Denpasar Selatan with a sample of 49 people, according to the inclusion criteria, with a non-probability sampling technique. The research instrument is a questionnaire with 32 items. The results of the knowledge analysis showed that some respondents had sufficient knowledge (53.1%), good knowledge (34.7%) and poor knowledge (12.2%). The results of the analysis between age and knowledge show that respondents aged < 20 years have less knowledge (33.3%), respondents aged 20-35 years have good knowledge (94.1%), sufficient (92.3%) and less ( 66.7%). Respondents aged >35 years had good (5.9%) and sufficient (7.7%) knowledge. The results of the analysis between parity and knowledge showed that primiparous respondents had good (5.9%) sufficient (50.0%) and poor (66.7%) knowledge. Multiparous respondents had good (94.1%), sufficient (50.0%) and poor (33.3%) knowledge. The majority of pregnant women's knowledge about postpartum contraception has sufficient knowledge, knowledge based on age and parity is categorized as having good knowledge. Suggestions for promoting family planning programs and providing outreach to PUS to increase family planning knowledge